Hybrid robotic thoracic surgery for excision of large mediastinal masses - Amore, Dario (J Vis Surg, 2018)
Between April 2016 and October 2017, we retrospectively reviewed all patients undergoing excision of large mediastinal masses using a hybrid robotic thoracic approach at the Unit of Thoracic Surgery of Monaldi Hospital in Naples. The inclusion criteria for this approach were: evident unilateral predominance of the mass; absence of invasion to surrounding structures. Planned conversion to sternotomy was necessary in one patient for tenacious adhesions between the mediastinal goiter and the left innominate vein. In all cases the postoperative course was uneventful. The hybrid robotic approach, adopted in our Unit, consists of a thoracic procedure performed completely with articulated surgical instruments under three-dimensional vision and followed by final extension of a port-site incision to retrieve the voluminous specimen. This approach uses all the advantages of robotic technology that enables to perform a fine dissection in the small space of the anterior mediastinum and at the same time, through the simple extension of a minimally invasive access, avoids the painful sequelae of thoracotomy. In selected cases, with increased experience in robotic surgery, it can be proposed for excision of large mediastinal masses, although a longer follow-up period is necessary to validate our findings.